Hubungan Sanitasi Lingkungan Rumah dengan Kejadian Penyakit ISPA pada Balita di Desa Tuapukan Kecamatan Kupang Timur Kabupaten Kupang - Frans, Yulita C.; Purimahua, Sintha L.; Junias, Marylin S. (Faculty of Public Health, Nusa Cendana University, 2019)
Acute Respiratory Infections (ARI) are infectious diseases that cause one and better parts of the channel (alveolus) including the adnexal tissue, such as sinuses, ear cavities, and pleura. Environmental saturation is an activity aimed at improving and maintaining standard environmental condition fundamentals that affect humans. Improper home sanitation is associated with high health problems, such as acute respiratory infections. The purpose of this study is to determine the relationship between the home environment with the incidence of ARI disease in Tuapukan Village, Kupang Timur Sub-district, Kupang District. This study uses an observational method with cross-sectional study design. The population of this study was 519 and the sample was 81. The bivariate analysis used Chi-Square statistical test with 95% significance level. The results shows that variables related to ARI occurrence were house wall (p=0,029), house ventilation (p=0,011), house lighting (p=0,003), occupancy density (p=0,021) and smoking habit (p=0.002). It is recommended that the societies should keep the cleanliness of the house so it will not be a place for the growth of germs; thus the societies are able to prevent ARI disease.